Suomalaisten terveys - Aromaa, Jussi; Apter, Dan.; Aromaa, Arpo.; Koskinen, Seppo; Huttunen, Jussi; Teperi, Juha. ([Helsinki] : Duodecim, 2005)
Abstract.
HYjulki
Hb0511
Keywords: public health; health status; health promotion; health behavior; delivery of health care; environmental health; kansanterveys; terveys; suomalaiset; terveydentila; terveyden edistäminen; sairastavuus; elintavat; elinolot; kuolleisuus; sairaudet; terveyspalvelut; sosiaalipalvelut; sosiaaliturva; väestö; terveyskäyttäytyminen; toimintakyky; terveyspolitiikka; terveydenhuolto; folkhälsa; hälsa; finländare; hälsotillstånd; hälsofrämjande; sjukfrekvens; levnadsvanor; levnadsförhållanden; mortalitet; sjukdomar; hälsovårdstjänster; social service; socialskydd; befolkning; hälsobeteende; funktionsförmåga; hälsopolitik; hälso- och sjukvård; Suomi; Finland